Maternal Risk Factors, Clinical Profile and Short-Term Outcome of Pre-Term Low Birth Weight Babies (KYAMC Journal, 2020)
Background: Preterm Low Birth Weight babies carry relatively higher risk of perinatal and neonatal mortality, retarded growth and development subsequently. In this study, some maternal risk factors were investigated as it seems to be important to study these factors on regional basis.Objective: To find out the maternal risk factors, clinical profile and short term outcome of pre-term low birth weight neonates by gestational age, birth weight, Occipitofrontal Circumference, length, different presentation (asphyxia, hypothermia, feeding difficulties, signs of infection) on admission and the morbidity and mortality of preterm LBW.Materials and Methods: A descriptive type of cross sectional study was done in neonatal ward of Jalalabad Ragib Rabeya Medical College Hospital, Sylhet from May, 2015 to April, 2016. Hundred cases were selected from neonatal ward and 100 controls were selected from obstetrics ward.Results: Among 100 pre-term LBW neonates, 52 were male and 48 were female. Only 22% mother took regular antenatal check up in case group and 55% in control group. Mean gestational age of neonates were 33.3±2.1 weeks. Important risk factors were primi parity (58% in cases vs 34% in control), hypertension (19% vs 5%), pre-eclampsia (26% vs 12%), prolonged rupture of membrane (33% vs 7%), APH (22% vs 0%), acute infection (8% vs 1%), multiple birth (17% vs 2%). Common clinical presentations were prematurity and LBW. Commonest morbidity was feeding problem (70%). The overall survival rate was 87%. Most common cause of death was septicemia (30%).Conclusion: all the identified risk factors were significantly higher in pre-term LBW babies than those of control.KYAMC Journal Vol. 11, No.-2, July 2020, Page 77-82